Reduced fronto-amygdalar connectivity in adolescence is associated with increased depression symptoms over time. (30th August 2017) - Scheuer, Hannah; Alarcón, Gabriela; Demeter, Damion V.; Earl, Eric; Fair, Damien A.; Nagel, Bonnie J.
Abstract: Depression is common among adolescents, affecting greater than 12% of youth in a given year. Studies have shown aberrant amygdala connectivity in depressed adolescents, compared with controls; however, no studies have examined whether these abnormalities precede and heighten risk for depressive symptom expression. This study used resting state functional connectivity (RSFC) magnetic resonance imaging to examine neurobiological markers of escalating depression symptoms in adolescents (ages 12–16 years; free from psychopathology at baseline). Of a large sample of adolescents, 18 showed ≥ 1 S.D. increase in depression scale t-scores over time ("escalators"; time to escalation ranging from 6 to 54 months in follow up) and were matched and compared to 19 youth showing stable CDI scores over time ("controls"). Whole-brain analyses on baseline RSFC data using an amygdala seed region-of-interest (ROI) showed that controls had greater RSFC, relative to escalators, between the right amygdala and left inferior frontal and supramarginal gyrus and right mid-cingulate cortex. Additionally, relative to escalators, control youth had less RSFC between the left amygdala and cerebellum. Findings suggest a possible neurobiological marker of increasing depressive symptoms during adolescence, characterized in part by reduced fronto-limbic connectivity, suggesting a premorbid deficiency in top-down emotional regulation. Highlights: Prospective longitudinal studies of youth provide premorbid indicators of risk. Functional connectivity profiles can serve as a neurobiological marker of risk. Premorbid fronto-limbic connectivity is associated with depression in youth.